2019
DOI: 10.1021/acs.cgd.9b01092
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Effects on Fullerene/Porphyrin Cocrystallization

Abstract: This investigation presents a systematic examination of the late transition metal octaethylporphyrins MII(OEP) with M = Co, Ni, Cu, and Zn as cocrystallization agents for C60. In each case, the fullerene was dissolved in benzene and then layered over an equimolar dichloromethane solution of the porphyrin. A striking new columnar structural type for these systems is found for CoII(OEP) and ZnII(OEP) with stoichiometric ratios 6:5 for porphyrin/fullerene. In these cocrystals, one fullerene is surrounded by two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Although cocrystallization of fullerenes with Ni II (OEP) has been used to determine the structures of endohedral fullerenes and fullerenes with holes in their surface , by many different research groups, there are several factors that are involved in crystal growth, including the role of the specific metal ion in the porphyrin and the solvents and other variables in the crystallization process. Recently, we demonstrated that cocrystallization of C 60 with M II (OEP) with M = Co, Ni, Cu, and Zn showed significant differences among the four different metalloporphyrins . For example, cocrystallization of Co II (OEP) and Zn II (OEP) with C 60 from a benzene/dichloromethane mixture produced the remarkable crystals 6Co II (OEP)­·5C 60 ·5CH 2 Cl 2 and 6Zn II (OEP)­·5C 60 ·5CH 2 Cl 2 , henceforth designated as 6:5Co and 6:5Zn respectively, that contained one C 60 molecule sandwiched between two porphyrin molecules in a clam shell arrangement, one C 60 molecule adjacent to only one porphyrin molecule, and one C 60 molecule that made no contact with any porphyrin as seen in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Although cocrystallization of fullerenes with Ni II (OEP) has been used to determine the structures of endohedral fullerenes and fullerenes with holes in their surface , by many different research groups, there are several factors that are involved in crystal growth, including the role of the specific metal ion in the porphyrin and the solvents and other variables in the crystallization process. Recently, we demonstrated that cocrystallization of C 60 with M II (OEP) with M = Co, Ni, Cu, and Zn showed significant differences among the four different metalloporphyrins . For example, cocrystallization of Co II (OEP) and Zn II (OEP) with C 60 from a benzene/dichloromethane mixture produced the remarkable crystals 6Co II (OEP)­·5C 60 ·5CH 2 Cl 2 and 6Zn II (OEP)­·5C 60 ·5CH 2 Cl 2 , henceforth designated as 6:5Co and 6:5Zn respectively, that contained one C 60 molecule sandwiched between two porphyrin molecules in a clam shell arrangement, one C 60 molecule adjacent to only one porphyrin molecule, and one C 60 molecule that made no contact with any porphyrin as seen in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effect of the metal ion in the porphyrin and the role of the solvent in the crystallization of C 60 /MOEP (M=Co, Ni, Cu, and Zn) was thoroughly investigated. 18,19 However, the temperature driven fullerene molecule dynamics in the crystal lattice of co-crystals with MOEP are still unclear for this type of fullerene. The structure of the nitride clusterfullerene Sc 3 N@C 80 was reported more than two decades ago.…”
mentioning
confidence: 99%
“…3,3',5,5'-tetra(9H-carbazol-9-yl)-1,1'-biphenyl (TCBP) was synthesized via a typical Suzuki coupling reaction from 9,9'-(5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1,3-phenylene)bis(9Hcarbazole) and 9,9'-(5-bromo-1,3-phenylene)bis(9H-carbazole) according to the reported literature. [23b] The 1 H NMR, 13 C NMR and MS (MALDI-TOF) spectra of DCB and TCBP are shown in Figure S11-S16. All solvents were HPLC grade.…”
Section: Experimental Section Materials and Chemical Reagentsmentioning
confidence: 99%
“…Fullerene‐porphyrin association has also been proven useful as a structure‐defined tool to produce strong π ‐ π interactions and covalent conjugations between the ring juncture of fullerene and electropositive center of porphyrin [12] . Additionally, metal coordination enables metalloporphyrins prevalent cocrystallization with almost any fullerene [13] . Meanwhile, better orbital overlapping between hetero‐fragments has been achieved upon the introduction of metal ions, which could enhance ambipolar mobility [14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation